СОЦИАЛЬНО-КУЛЬТУРНЫЕ ФАКТОРЫ ФОРМИРОВАНИЯ МОЛОДЁЖНОЙ ЛЕКСИКИ (НА МАТЕРИАЛЕ НЕМЕЦКОГО ЯЗЫКА) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
The article is devoted to the analysis of the concept of youth vocabulary in linguistic science based on the material of the German language. Drawing on the works of leading German sociolinguists (E. Neuland, N. Balo, H. Henne, J. Androutsopoulos), as well as the data from the annual “Youth Word of the Year” (Jugendwort des Jahres) competition organized by the Langenscheidt publishing house, the paper examines theoretical approaches to the definition of Jugendsprache. Special attention is paid to the distinctions between youth vocabulary, slang, and jargon, the main functions (identificational, expressive, communicative, and innovative), as well as characteristic features such as high variability, emotionality, creativity, and dependence on the sociocultural context. The study also analyzes factors such as the influence of globalization and the English language, digital